Analisis Perkembangan dan Tantangan Bank Syariah Dalam Persaingan Dengan Bank Konvensional di Pasar Keuangan Modern - Fauzatul Laily Nisa; Krisna Reswara (Jurnal Ekonomi dan Pembangunan Indonesia, 2024)
Technological developments in Indonesia have experienced a significant surge in recent years. Technological developments in Indonesia also have a positive impact on sharia banking. As a result, sharia banking in Indonesia is not only able to compete with conventional banking, but also contributes to overall economic stability and financial inclusion, strengthening Indonesia's position as one of the global sharia financial centers. However, even though Islamic banks are experiencing rapid development with the support of digital technology, there will certainly be developments and challenges that will be faced by Islamic banks themselves. The development of Islamic Banking has demonstrated its relevance in the global financial discourse with an increasingly expanding role, based on the principles of ethics and financial justice. To overcome these challenges, Islamic banks can take strategic steps.